2014
DOI: 10.1007/s00270-014-1015-x
|View full text |Cite
|
Sign up to set email alerts
|

Regional Radiation Pneumonitis After SIRT of a Subcapsular Liver Metastasis: What is the Effect of Direct Beta Irradiation?

Abstract: We herein present a patient undergoing selective internal radiation therapy with an almost normal lung shunt fraction of 11.5%, developing histologically proven radiation pneumonitis. Due to a predominance of pulmonary consolidations in the right lower lung and its proximity to a large liver metastases located in the dome of the right liver lobe a Monte Carlo simulation was performed to estimate the effect of direct irradiation of the lung parenchyma. According to our calculations direct irradiation seems negl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…SIRT is an established treatment modality for chemoresistant, unresectable, primary, or metastatic hepatic malignancies. During the development phase of this therapeutic modality, tumor-induced arteriovenous pulmonary shunting and possible occurrence of RP emerged as potential limitations of the technique [ 2 , 4 , 24 26 ]. Post-treatment development of interstitial pneumonia and presence of micro-spheres in the lung biopsy were reported by Lin et al in 1994 in a hepatocellular carcinoma patient who was treated with resin micro-spheres and who had a pulmonary shunt of 17% [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SIRT is an established treatment modality for chemoresistant, unresectable, primary, or metastatic hepatic malignancies. During the development phase of this therapeutic modality, tumor-induced arteriovenous pulmonary shunting and possible occurrence of RP emerged as potential limitations of the technique [ 2 , 4 , 24 26 ]. Post-treatment development of interstitial pneumonia and presence of micro-spheres in the lung biopsy were reported by Lin et al in 1994 in a hepatocellular carcinoma patient who was treated with resin micro-spheres and who had a pulmonary shunt of 17% [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…After that, Leung et al reported the death of three out of five patients developing RP after SIRT [ 2 ]. While Salem et al observed no clinical radiation pneumonitis in a total of 58 patients receiving higher-than-recommended doses (> 30 Gy) [ 4 ], Dobrocky et al published a case report where an asymptomatic patient had radiation pneumonitis within 3 months following treatment as confirmed both by imaging modalities and lung biopsy [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Comparison of the planar scintigraphic images of the case (1a, 1b) and reference patient for liver-lung shunt imaging and transaxial fluorine-18 fluorodeoxyglucose positron emission tomography (18F-FDG PET/CT-1e 1E) / computed tomography (CT-1c, 1d, 1f) images obtained after selective internal radiation therapy (SIRT) RP [15]. Dobrocky et al published a case report without related DLCO values where an asymptomatic patient had RP as confirmed both by imaging modalities and histopathologic evaluation [9].…”
Section: Discussionmentioning
confidence: 99%
“…After this case report, Leung et al stated the mortality rate of 60% in five patients who developed RP after the same treatment [3]. In 2015, another asymptomatic patient who was diagnosed with RP after SIRT as verified both by histopathologic examination and imaging findings was published by Dobrocky et al [9].…”
Section: Introductionmentioning
confidence: 95%